2017
DOI: 10.1038/s41598-017-05709-y
|View full text |Cite|
|
Sign up to set email alerts
|

Defective Sphingosine-1-phosphate metabolism is a druggable target in Huntington’s disease

Abstract: Huntington’s disease is characterized by a complex and heterogeneous pathogenic profile. Studies have shown that disturbance in lipid homeostasis may represent a critical determinant in the progression of several neurodegenerative disorders. The recognition of perturbed lipid metabolism is only recently becoming evident in HD. In order to provide more insight into the nature of such a perturbation and into the effect its modulation may have in HD pathology, we investigated the metabolism of Sphingosine-1-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 73 publications
4
82
0
Order By: Relevance
“…We have recently reported that sphingolipid metabolism is aberrant in HD (Di Pardo et al, 2017a ). Here, in order to provide a clearer picture of the deranged sphingolipid homeostasis in the disease, we investigated any potential alteration of the de novo biosynthetic pathway of these lipids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported that sphingolipid metabolism is aberrant in HD (Di Pardo et al, 2017a ). Here, in order to provide a clearer picture of the deranged sphingolipid homeostasis in the disease, we investigated any potential alteration of the de novo biosynthetic pathway of these lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence indicates that defective sphingolipid metabolism may likely contribute to different neurodegenerative conditions, including HD (Desplats et al, 2007 ; Maglione et al, 2010 ; Ceccom et al, 2014a , b ; Couttas et al, 2014 , 2016 ; Di Pardo et al, 2016 , 2017a ). We and others have recently demonstrated that alterations in the sphingolipid metabolism occur early in the disease stage and may play, therefore, a critical role in the pathogenesis of HD (Di Pardo et al, 2016 , 2017a ; Skene et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene therapy using a stereotaxic injection of adeno-associated virus (AAV)rh10 viral constructs for GFP or human CYP46A1 restored CYP46A1 levels in striatal neurons of R6/2 mice and increasing neuronal survival through production of sterols laneosterol and desmosterol, metabolites of CYP46A1 processing, and reestablishment of normal cholesterol levels [ 93 ]. Sphingosine-1-phosphate metabolism in HD patients and two rodent models has shown aberrant signaling of intermediates and metabolizing enzymes, with increased expression of sphingosine-1-phosphate lyase and decreased expression of sphingosine kinase 1/2 in the striatum of post-mortem humans and HD transgenic models, both in early and late stages of the HD rodent model [ 94 ]. Decreasing the bioavailability of sphingosine-1-phosphate could dismantle downstream signaling from G-protein coupled receptors sphingospine-1-phosphate receptors 1–5 [ 95 ] of which S1PR2 has been shown to have expression in neurons [ 62 ].…”
Section: Bile Acids In Neurodegenerative Diseasesmentioning
confidence: 99%